If x2 + 4y2 + 9z2 – 6yz - 3zx - 2xy = 0, then
please say this qnswer
Answers
Answered by
0
ANSWER
x
2
+4y
2
+9z
2
−6yz−3zx−2xy
=
2
1
((x−2y)
2
+(2y−3z)
2
+(3z−x)
2
)
This is the sum of 3 squares. So this term is greater than or equal to 0.
Equality occurs when, x=2y, 2y=3z, 3z=x
Answered By
Answered by
0
Step-by-step explanation:
x²+(2y)²+(3z)² - 2xy - 6yz -3zx = 0
multiply by 2 on both sides
2x² + 2(2y)² +2(3z)² - 2(2xy) - 2(6yz)-2(3zx) = 0
x² -2*x*2y +(2y)² +
(2y)² -2*2y*3z+(3z)² +
(3z)² -2*3z*x + x² =0
(x-2y)² +
(2y - 3z)² +
(3z - x)² =0
sum of 3 squares is zero implies each term is zero
= x-2y=0
2y-3z=0
3z-x=0
x=2y =3z
Similar questions